ANALISIS BIAYA SUMBERDAYA DOMESTIK PADA USAHA PENGGEMUKAN SAPI POTONG - Ridwan Lutfiadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2005)
The government has launched policies to let Jeedlotters import the cattle to he fattened and also allow some companies to import frozen beef for special segment market. This research was conducted to know, how the Inkud Satwa Nusantara have the comparative advantage to tvns the business operation of feedhtting. Domestic resources cost analysis is used to determine the comparative advantage. The research concluded that the coeficien of domestic resources cost < 1, so the operation of feedhtting using the cattle import still efficient, and have the comparative advantage.